Targeted Degradation of Transcription Coactivator SRC‐1 through the N‐Degron Pathway. Issue 40 (12th August 2020) - Lee, Yeongju; Heo, Jiwon; Jeong, Hoibin; Hong, Kyung Tae; Kwon, Do Hoon; Shin, Min Hyeon; Oh, Misook; Sable, Ganesh A.; Ahn, G‐One; Lee, Jun‐Seok; Song, Hyun Kyu; Lim, Hyun‐Suk
Abstract: Aberrantly elevated steroid receptor coactivator‐1 (SRC‐1) expression and activity are strongly correlated with cancer progression and metastasis. Here we report, for the first time, the development of a proteolysis targeting chimera (PROTAC) that is composed of a selective SRC‐1 binder linked to a specific ligand for UBR box, a unique class of E3 ligases recognizing N‐degrons. We showed that the bifunctional molecule efficiently and selectively induced the degradation of SRC‐1 in cells through the N‐degron pathway. Importantly, given the ubiquitous expression of the UBR protein in most cells, PROTACs targeting the UBR box could degrade a protein of interest regardless of cell types. We also showed that the SRC‐1 degrader significantly suppressed cancer cell invasion and migration in vitro and in vivo. Together, these results demonstrate that the SRC‐1 degrader can be an invaluable chemical tool in the studies of SRC‐1 functions. Moreover, our findings suggest PROTACs based on the N‐degron pathway as a widely useful strategy to degrade disease‐relevant proteins. Abstract : A PROTAC composed of a selective stapled peptide for transcription coactivator SRC‐1 linked to a specific ligand for UBR E3 ligase induces the selective degradation of SRC‐1. This first‐in‐class SRC‐1 degrader efficiently impairs SRC‐1‐mediated transcription and suppresses cancer cell invasion and migration in vitro and in vivo and holds promise as an invaluable tool to probe SRC‐1 functions.